The Effect of Cellulose Succinate Concentration on the Mechanical Properties of Bioplastics - Jannah, Miftahul; Mustapa; Utami, Aisyiah Restutiningsih Putri; Papriani, Nada Pertiwi (Al-Kimia, 2023)
The principle of bioplastic film formation is based on hydrogen bonds between the constituent molecules of bioplastics. The addition of carboxylic groups to cellulose molecules into cellulose succinate (CS) can increase bond regularity so that it has an impact on the mechanical properties of bioplastics. The purpose of this study was to determine the effect of CS concentration on tensile strength and elongation of bioplastics. The stages of this research are the synthesis of bioplastics by mixing method and variation of CS concentration, characterization of bioplastics to determine the effect of CS concentration on the mechanical properties of bioplastics, analysis of functional groups with FTIR and bond regularity with XRD. The results obtained in this study are CS concentration affects the characteristics of bioplastics. The best bioplastic was found at 3.2% CS concentration with a tensile strength value of 10.48 MPa and elongation of 4.38%. The peaks that appear on FTIR analysis are typical groups on cellulose, namely O-H, C-H and C-O. CS bioplastics also consist of amorphous and crystalline phases.